Design of digital twin applications in automated storage yard scheduling. (January 2022) - Gao, Yinping; Chang, Daofang; Chen, Chun-Hsien; Xu, Zhenyu
Highlights: A digital twin-enabled automated storage yard scheduling framework is proposed. Three subsystems focused on main resources is included in the framework. Key technologies are introduced for the digital twin-enabled system. Digital twin and simulation optimization are applied in the uncertain scheduling. The case of ASC scheduling demonstrates the effectiveness of the proposed framework. Abstract: A digital twin-enabled automated storage yard scheduling framework for uncertain port dispatching is proposed in this paper. Digital twin technology is employed to establish the virtual yet realistic storage yard and the connection between them. In the proposed framework, disturbed scenarios during practical operation are monitored, and real-time data is visualized in the virtual space to adapt to the time-varying environment. The proposed framework focuses on the optimization of three main resources, viz. storage area, automated stacking cranes (ASCs), and automated guided vehicles (AGVs). In addition, three key technologies, the Internet of Things (IoT), virtual reality, and digital thread, are adopted to develop the proposed scheduling system. A case study of ASC rescheduling due to dynamic arrival is used to demonstrate the effectiveness of the proposed framework and the significance of obtaining uncertainties in port optimization. Sensitivity analysis is conducted to define the appropriate configuration required to handle all tasks. The results show that digital twin applications in automated storage yard scheduling help operators make optimization decisions.